2004
DOI: 10.1128/aem.70.12.7404-7412.2004
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl Precipitation byPseudomonas aeruginosavia Controlled Polyphosphate Metabolism

Abstract: The polyphosphate kinase gene from Pseudomonas aeruginosa was overexpressed in its native host, resulting in the accumulation of 100 times the polyphosphate seen with control strains. Degradation of this polyphosphate was induced by carbon starvation conditions, resulting in phosphate release into the medium. The mechanism of polyphosphate degradation is not clearly understood, but it appears to be associated with glycogen degradation. Upon suspension of the cells in 1 mM uranyl nitrate, nearly all polyphospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 62 publications
0
51
1
4
Order By: Relevance
“…The tolerance to U exhibited by gram-positive and gramnegative microorganisms may be explained by several different cellular mechanisms, as previously reported by other investigators (30,49,55). One mechanism, bioadsorption, has recently been hypothesized to occur in a well-characterized Arthrobacter type strain, the A. nicotianae type strain (59).…”
Section: Vol 72 2006 Horizontal Gene Transfer Of P Ib -Type Atpasesmentioning
confidence: 62%
“…The tolerance to U exhibited by gram-positive and gramnegative microorganisms may be explained by several different cellular mechanisms, as previously reported by other investigators (30,49,55). One mechanism, bioadsorption, has recently been hypothesized to occur in a well-characterized Arthrobacter type strain, the A. nicotianae type strain (59).…”
Section: Vol 72 2006 Horizontal Gene Transfer Of P Ib -Type Atpasesmentioning
confidence: 62%
“…Electron microscopy analyses of cells exposed to these elements demonstrated intracellular localization with phosphate-rich granules, suggesting that contaminant sequestration may be achieved by polyphosphates and may protect sensitive cytosolic molecules from oxidative damage. In addition to polyphosphate chelation of metals and radionuclides, an engineered Pseudomonas aeruginosa strain overexpressing the ppk gene was shown to enhance intracellular phosphate concentrations when compared to the wildtype strain [133]. Upon nutrient starvation, polyphosphate depolymerization and efflux of phosphate into the media containing U(VI) promoted the removal of 80% of the soluble U(VI) as a uranyl phosphate precipitate.…”
Section: Biological Approaches To Phosphate-mediated Immobilization Omentioning
confidence: 99%
“…In response to the local geochemistry of contaminated environments, production of intracellular polyphosphate provides microorganisms with a means to sequester toxic ions within the cell cytosol as well as the regulation of gene(s) expressed in response to cellular stress (e.g., DNA repair, RNA polymerase sigma factor, and pH extremes) [55,[127][128][129][130][131]. The reactivity of cytosolic polyphosphates has been shown to facilitate intracellular sequestration of Cd, Cu, Hg, Pb, U, and Zn in genetically engineered bacterial strains as well as naturally occurring archaeal and bacterial strains [52,55,[132][133][134][135][136]. Electron microscopy analyses of cells exposed to these elements demonstrated intracellular localization with phosphate-rich granules, suggesting that contaminant sequestration may be achieved by polyphosphates and may protect sensitive cytosolic molecules from oxidative damage.…”
Section: Biological Approaches To Phosphate-mediated Immobilization Omentioning
confidence: 99%
“…Such intracellular sequestration within phosphate-rich granules or polyphosphates decreases the intracellular U concentration thereby protecting sensitive cytosolic molecules from U toxicity (6,20,21). On the other hand, the hydrolysis or degradation of polyphosphates in response to heavy metals or nutrient stress has been proposed to precipitate heavy metals extracellularly, enabling metal detoxification (23,24). The overexpression of the polyphosphate kinase (ppk) gene in Pseudomonas aeruginosa results in the significant accumulation of polyphosphates which degrade under carbon-starved conditions, and the phosphates released therefrom precipitate uranyl out of the solutions (24).…”
mentioning
confidence: 99%
“…On the other hand, the hydrolysis or degradation of polyphosphates in response to heavy metals or nutrient stress has been proposed to precipitate heavy metals extracellularly, enabling metal detoxification (23,24). The overexpression of the polyphosphate kinase (ppk) gene in Pseudomonas aeruginosa results in the significant accumulation of polyphosphates which degrade under carbon-starved conditions, and the phosphates released therefrom precipitate uranyl out of the solutions (24). Several environmental strains, such as Cellulomonas, Arthrobacter, Rahnella, and Bacillus, isolated from contaminated subsurface soils of the Department of Energy's Field Research Centre (ORFRC) were shown to immobilize uranium as a biogenic phosphate mineral resulting from polyphosphate metabolism or organophosphate hydrolase activity (25)(26)(27).…”
mentioning
confidence: 99%